Laser surface modification of gray cast iron using ND: YAG laser for enhanced surface properties - Mohd Norfaez, Ismail (2013)
This report presents laser surface modification on gray cast iron using Nd: YAG laser for enhanced surface modification. Material used in this work was gray cast iron from automotive brake disc. Experiments were performed using was Nd: YAG pulsed laser under different processing conditions. The parameters of interest were the laser peak power of 670 W, 800 W, 1000 W, Pulse repetition frequency of 50 Hz, 60 Hz, 70 Hz and travel speed 1000 mm/min, 1200 mm/min, 1400 mm/min. Various modification layers of gray cast iron were analyzed with respect to microstructure, hardness value, hardening depth, and surface roughness. Results of laser incidence under different processing conditions are presented. Different microstructure achieved by applying range of laser treatment selected parameter. A good increase of micro hardness in the entire performed test was verified at Peak power of 830 W, speed and pulse repetition frequency of 1400 mm / min and 50 Hz respectively. A minimum depth at 134.262 μm and maximum hardness at 423.014 HV0.3 was produced. These findings were important to increase wear resistant of brake disc surface.